Correlates of physical activity among community-dwelling adults aged 50 or over in six low- and middle-income countries. - Ai Koyanagi; Brendon Stubbs; Lee Smith; Benjamin Gardner; Davy Vancampfort (PLoS ONE, 2017)
Considering that physical activity is associated with healthy ageing and helps to delay, prevent, or manage a plethora of non-communicable diseases in older adults, there is a need to investigate the factors that influence physical activity participation in this population. Thus, we investigated physical activity correlates among community-dwelling older adults (aged ≥50 years) in six low- and middle-income countries.Cross-sectional data were analyzed from the World Health Organization's Study on Global Ageing and Adult Health. Physical activity was assessed by the Global Physical Activity Questionnaire. Participants were dichotomized into low (i.e., not meeting 150 minutes of moderate physical activity per week) and moderate-to-high physically active groups. Associations between physical activity and a range of correlates were examined using multivariable logistic regressions.The overall prevalence (95%CI) of people not meeting recommended physical activity levels in 34,129 participants (mean age 62.4 years, 52.1% female) was 23.5% (22.3%-24.8%). In the multivariable analysis, older age and unemployment were significant sociodemographic correlates of low physical activity. Individuals with low body mass index (<18.5kg/m2), bodily pain, asthma, chronic back pain, chronic obstructive pulmonary disease, hearing problems, stroke, visual impairment, slow gait, and weak grip strength were less likely to meet physical activity targets in the overall sample (P<0.05). The associations varied widely between countries.Our data illustrates that a multitude of factors influence physical activity target achievement in older adults, which can inform future interventions across low- and middle-income countries to assist people of this age group to engage in regular physical activity. Future prospective cohort studies are also required to investigate the directionality and mediators of the relationships observed.